Coefficient comparison technique for identifying the fault types in underground cable - Ngaopitakkul, A.; Kaitwanidvilai, S.; Apisit, C. (My University, 2010)
This paper proposes a novel comparison technique for identifying the phase with fault appearance in underground cable using Discrete Wavelet Transform. The Wavelet transform has been employed to extract high frequency components superimposed on fault signals simulated using ATP/EMTP. The fault type algorithm is constructed on the basis of coefficient comparison from signals decomposed from Discrete Wavelet Transform. Various cases studies based on Thailand electricity distribution underground systems have been investigated so that the algorithm can be implemented. It is found that the proposed method can indicate the fault types with satisfactory accuracy. ©2010 IEEE.
Keywords: ATP/EMTP; Distribution underground cable; Wavelet transform